Study of Students' Psychological Influence on Square-shaped Learning Classrooms in Unmuha Architecture Department Unmuha - Annisa, Astrid; Marlina, Henny; Verdinal, Teuku Zafran Farras (Department of Architecture, Faculty of Engineering, University of Muhammadiyah Aceh, 2024)
A satisfying social and personal life will be realized through education, and the educational process will shape students' character. The Architecture Department, Faculty of Engineering, University of Muhammadiyah Aceh is a department that conducts direct learning in both theory classes, laboratories, and design studio rooms. As part of educational facilities, the existence of a classroom is an important element in the learning process, the comfort of the classroom affects the level of focus and concentration of students in teaching and learning activities in the classroom. This study aims to examine the influence of the square shape of the classroom on the psychological comfort of students and identify the factors that affect the psychological comfort of students in Architecture Department. Using qualitative methods through observation to study objects in the form of a square shaped learning classroom of Architecture Department. Literature study is used to explore previous research, regulations and standards related to this research. Indicators used to assess students' psychological comfort are physical environmental factors, and psychological factors. Physical environmental factors in the form of lighting and spatial layout, while psychological factors related to focus, comfort and positive feelings felt by students, so that effective learning can be created. The results showed that, the shape of the classroom has a significant influence on the psychological comfort of students where the capacity of the RKB at the Architecture Department, Faculty of Engineering, University of Muhammadiyah Aceh which exceeds the standard and the lack of flexibility of the layout has a negative impact on student comfort.